Reconstructing Management Epistemology through Maqasid al-Shariah: Towards an Integrative Framework Beyond Positivism - Irfan Harmoko; Abdelmounaim Graiguer (Islamika Inside: Jurnal Keislaman dan Humaniora, 2026)
The dominance of positivist epistemology has profoundly shaped management science by privileging empirical objectivity, instrumental rationality, and value-neutral inquiry as the primary standards of scientific legitimacy. While this paradigm has contributed substantially to methodological rigor, it has also marginalized ethical, spiritual, and teleological dimensions that are essential for understanding complex organizational realities. Existing studies commonly employ maqasid al-shariah as a normative framework for evaluating managerial practices; however, its potential as a foundation for reconstructing management epistemology remains underdeveloped. This study aims to reconstruct the epistemological foundations of management science through maqasid al-shariah by developing an integrative epistemological framework that transcends the limitations of positivism. Employing an integrative conceptual synthesis, the study combines thematic analysis, comparative epistemological analysis, and conceptual reconstruction to critically examine positivist assumptions and synthesize alternative epistemic foundations derived from Islamic epistemology and maqasid al-shariah. The findings demonstrate that maqasid al-shariah should not be understood merely as an ethical framework but as an epistemic principle governing the construction, interpretation, validation, and application of management knowledge. The proposed framework integrates revelation, reason, and empirical inquiry into a coherent epistemological architecture that preserves the analytical strengths of empirical investigation while embedding knowledge production within the higher objectives of Islamic thought. Rather than replacing positivism, the framework reconstructs its epistemological boundaries by incorporating ethical rationality and purposive knowledge into scientific inquiry. This study contributes to the philosophy of management by offering an original integrative epistemological framework that enriches contemporary debates on management epistemology, Islamic philosophy of knowledge, and epistemological pluralism beyond positivist assumptions.